Pelecehan Seksual Menurut Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual Di Lingkungan Kampus Universitas Palangka Raya - Rahmadani, Siti Amalia; Suriani, Rollys; Ali, Nuraliah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The enactment of Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) aims to provide comprehensive protection for victims of sexual violence, including in higher education institutions. This study aims to evaluate the implementation of UU TPKS at the University of Palangka Raya (UPR), specifically assessing campus preparedness, the effectiveness of reporting mechanisms, the level of awareness among the academic community, and identifying socio-cultural challenges in its enforcement. A normative legal research approach was employed by analyzing relevant legal norms, regulations, and doctrines related to campus sexual harassment. The findings reveal that the reporting system for sexual violence at UPR remains suboptimal. Victims are often reluctant to report due to fears of social stigma, academic repercussions, and lack of trust in existing mechanisms. The level of awareness among students and lecturers regarding UU TPKS and its protective measures is still low, further hindering the effective enforcement of the law. Socio-cultural barriers, such as patriarchal norms and victim-blaming, exacerbate the situation. This study concludes that strengthening a secure and confidential reporting system is crucial, accompanied by increased awareness through continuous socialization programs. Collaboration with external institutions is essential to support victims and create an inclusive, victim-oriented system. Additionally, the university must address cultural barriers by fostering a transformation toward an academic culture free from sexual violence. Effective implementation of UU TPKS requires a holistic approach integrating law enforcement, institutional support, and cultural change to create a safe and just campus environment for the entire community.